Vacancy-doped homojunction structural TiO2 nanorod photoelectrodes with greatly enhanced photoelectrochemical activity. (25th January 2018) - Liu, Yichao; Ren, Fen; Shen, Shaohua; Chen, Jianan; Fu, Yanming; Cai, Guangxu; Wang, Xuening; Xing, Zhuo; Wu, Liang; Zheng, Xudong; Jiang, Changzhong
Abstract: In this study, we report a simple, effective and universal approach to fabricate homojunction structural TiO2 nanorod array photoelectrodes through doping of gradient distributed oxygen vacancies introduced by annealing in high vacuum with controlled time. The homogeneous junction structure promotes the separation and transport of photoexcited charge carriers, and the photocurrent density of TiO2 nanorod arrays annealed in high vacuum for 2 h was 20 times higher than that of the pristine TiO2 nanorod arrays. The results indicate that annealing in high vacuum with controlled time could form a homojunction structure, which is an effective approach for further enhancing the performance of UV–visible light driven photocatalytic materials for water splitting. Highlights: A simple, effective and universal approach to fabricate homojunction TiO2 . Gradient distributed VO were introduced by controlled annealing in vacuum. A 20 times enhancement of photocurrent density was achieved.